2007
DOI: 10.3758/bf03193490
|View full text |Cite
|
Sign up to set email alerts
|

Text repetition and text integration

Abstract: Two experiments explored the levels of text representation that mediate text repetition effects, following the Raney (2003) model. The magnitude of the repetition benefit in Experiment 1 supported predictions of Raney's model, indicating that the ease of forming a situation model contributed to the magnitude of the reprocessing benefit. In addition, representations organized around a good situation model were more sensitive to changes than were representations formed from reading without a good situation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…Manipulations of the elaboration of the repeated text indicate that when two passages do not share a theme, characters, or setting information, the repeated text must be salient for repetition effects to occur. Although the long-term priming effects (e.g., Sloman et al, 1988) and of text repetition effects across a 24-h delay (Collins & Levy, 2007), whereas there has been no evidence of this type of long-term meaning selection effect.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Manipulations of the elaboration of the repeated text indicate that when two passages do not share a theme, characters, or setting information, the repeated text must be salient for repetition effects to occur. Although the long-term priming effects (e.g., Sloman et al, 1988) and of text repetition effects across a 24-h delay (Collins & Levy, 2007), whereas there has been no evidence of this type of long-term meaning selection effect.…”
Section: Resultsmentioning
confidence: 95%
“…This occurred even though Story A and Story B were episodically distinct and even though the readers had no reason to believe that Story A and Story B made up a single trial. Furthermore, Klin et al (2007) demonstrated that the slow- is some evidence of text repetition effects across a 24-h delay (Collins & Levy, 2007). However, this was done with passages that had substantial overlap; 7 sentences were repeated across passages that were 15-17 sentences in length, and thus, there were many opportunities for readers to retrieve the original processing episode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations